2017
DOI: 10.1158/2159-8290.cd-16-1123
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ALK: Precision Medicine Takes on Drug Resistance

Abstract: Anaplastic lymphoma kinase (ALK) is a validated molecular target in several ALK-rearranged malignancies, including non-small-cell lung cancer (NSCLC). However, the clinical benefit of targeting ALK using tyrosine kinase inhibitors (TKIs) is almost universally limited by the emergence of drug resistance. Diverse mechanisms of resistance to ALK TKIs have now been discovered, and these basic mechanisms are informing the development of novel therapeutic strategies to overcome resistance in the clinic. In this Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
460
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(488 citation statements)
references
References 191 publications
6
460
0
4
Order By: Relevance
“…The implication of this clinical observation is that these FGFR2 resistance mutations may also drive intrinsic resistance to FGFR inhibitors and furthermore a similar mechanism of FGFR3 resistance mutations may drive acquired resistance to FGFR3-fusion expressing cancers in response to FGFR inhibition. The emergence of secondary FGFR resistant mutations is comparable to that observed in response to ALK inhibitors in ALK-fusion patients (16), suggesting a strategic approach of developing structurally optimized FGFR inhibitors may be required for durable responses in FGFR-driven cancers. In this strategy, a covalent mechanism may be an advantage based on the assumption that covalent inhibitors exhibit less susceptibility to resistance arising from mutations (17).…”
Section: Discussionmentioning
confidence: 96%
“…The implication of this clinical observation is that these FGFR2 resistance mutations may also drive intrinsic resistance to FGFR inhibitors and furthermore a similar mechanism of FGFR3 resistance mutations may drive acquired resistance to FGFR3-fusion expressing cancers in response to FGFR inhibition. The emergence of secondary FGFR resistant mutations is comparable to that observed in response to ALK inhibitors in ALK-fusion patients (16), suggesting a strategic approach of developing structurally optimized FGFR inhibitors may be required for durable responses in FGFR-driven cancers. In this strategy, a covalent mechanism may be an advantage based on the assumption that covalent inhibitors exhibit less susceptibility to resistance arising from mutations (17).…”
Section: Discussionmentioning
confidence: 96%
“…They proposed that in the setting of progression on a second-generation ALK inhibitor, repeat biopsy to assess for ALK mutations should be strongly considered as the presence of an ALK resistance mutation suggests that it remains the main oncogenic driver and the patient should be considered for further ALK -directed therapy. However, should the tumors not harbor ALK mutations, then other treatment strategies (i.e., combination chemotherapy) should be considered over ALK TKI monotherapy [8]. The data generated by Gainor et al is in patients who received next-generation ALK inhibitors after having received crizotinib.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Also Ou et al recently reported that the emergence of ALK -resistant mutations occurred more commonly in patients with variant 3 EML4-ALK rearrangement than in patients with variant 1 tumors [4]. Other rarer ALK fusions occur such as KIF5B-ALK [5], KLC1-ALK [6], and ALK-PTPN3 [7], but they collectively are less frequent than the ALK-EML4 rearrangement [8], and therefore little is known about their clinical significance with respects to different response to ALK TKIs. In general, patients with ALK -rearranged NSCLC tend to be younger, never smokers, and have lung adenocarcinoma, though rarely patients with other lung cancer histologies have also been found to harbor this mutation [9].…”
Section: Introductionmentioning
confidence: 99%
“…in the ALK domain and amplification of ALK (PMID, PMID, PMID, PMID) (31)(32)(33)(34). In addition, on-target acquired genomic alterations tumors can develop alternate pathway activation like MET and KIT amplifications, BRAF, NRAS, FGFR2, PIK3CA, IGF1R and ERBB family of receptor mutations (35)(36)(37)(38). This degree of heterogeneity, dynamic shifts in clonal cellular populations and polyclonal resistance mechanisms makes molecular work up for patients progressing on targeted therapy complicated.…”
Section: Identification Of Clinically Actionable Genomic Alterationsmentioning
confidence: 99%